Social entrepreneurship : leveraging economic, political, and cultural dimensions - Lundstrom, Anders, 1946-; Zhou, Chunyan; Friedrichs, Yvonne von; Sundin, Elisabeth (Cham, Switzerland : Springer, 2014)
Research from ten different countries on implementation, institutionalization and future prospects of social entrepreneurship, considering the needs of social and human development in the context of economy, politics, and cultural issues. By conceptualizing the notions of social entrepreneurship and societal entrepreneurship, this volume disseminates the latest findings in research and theory of social entrepreneurship that will be useful to educators, libraries, scholars, non-profit researchers, public policy makers, practitioners, students, and anyone interested in staying abreast of advances in this field. It is also an important reference source for conducting research in or teaching social entrepreneurship.
Part I. Rethinking social entrepreneurship -- Introduction / Anders Lundstr$1'Xl (Band Chunyan Zhou -- Soci(et)al entrepreneurship and different forms social enterprise / Malin Gawell -- A review of social entrepreneurship and social enterprises: a three-dimensional perspective / Anders Lundstr$1'Xl (Band Chunyan Zhou -- Part II. Implementing social entrepreneurship -- Entrepreneurial discovery and Asian entrepreneurship in the UK / Spinder Dhaliwal and David Deakins -- Corporate social responsibility in family versus non-family enterprises: an exploratory study / Giovanna Campopiano, Alfredo De Massis and Lucio Cassia -- What sustainable entrepreneurship looks like: an exploratory study from a student perspective / Katia Richomme-Huet and Julien de Freyman -- Developing entrepreneurial self-efficacy and intent: a case of social entrepreneurship / Jess Co and Sarah Cooper -- How can a health-care business achieve strategy elasticity in a crisis environment? / Jarmila $1"5.(Bbestovand Thomas M. Cooney.s
Includes bibliographical references.
Keywords: Social entrepreneurship; Social responsibility of business